An estimate of ⁴⁷Sc photonuclear yield in a production target - Dikiy, N.P.; Lyashko, Yu.V.; Shevchenko, V.A.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2020)
⁴⁷Sc is considered as a promising beta-emitter for cancer immunotherapy. For its carrier-free production, the ⁴⁸Ti(γ,p) ⁴⁷ Sc reaction in the field of bremsstrahlung radiation of an electron accelerator can be used. On the basis of developed analytical model and a double-foil activation technique, the main characteristics of the photonuclear isotope production and optimal dimensions of a production target have been established. The measured photonuclear yield of ⁴⁷Sc and dominant scandium admixtures in thin foils of natural titanium in the electron energy range of 35 to 95 MeV enabled to specify the available data on the cross-section of the ⁴⁸Ti(γ,p)⁴⁷Sc reaction. Using those results, the gross and specific activity of ⁴⁷Sc in the cylindrical titanium targets of optimal size were calculated by a simulation technique. The comparison of capacity of the photonuclear method of the ⁴⁷Sc production with other techniques is carried out. ⁴⁷Sc вважається перспективним бета-емітером в імунотерапії раку. Для виробництва ізотопу без носія може бути використана реакція ⁴⁸Ti (γ,p)⁴⁷Sc у полі гальмівного випромінення прискорювача електронів. На основі розробленої аналітичної моделі і методу сумісної активації двох фольг встановлені основні характеристики фотоядерного виробництва ізотопів та оптимальні розміри технологічної мішені. Одержані експериментальні дані щодо виходу ⁴⁷Sc і основних домішкових ізотопів скандію в тонких фольгах з природного титану в діапазоні значень енергії електронів 35…95 МеВ дозволяють уточнити наявні дані щодо перетину реакції ⁴⁸Ti(γ,p)⁴⁷Sc. На основі цих результатів методом моделювання розраховані загальна і питома активність ⁴⁷Sc у циліндричних мішенях з титану оптимального розміру. Проведено порівняння продуктивності фотоядерної технології виробництва ⁴⁷Sc з іншими методами. ⁴⁷Sc считается перспективным бета-эмиттером в иммунотерапии рака. Для производства изотопа без носителя может быть использована реакция ⁴⁸ Ti (γ,p)⁴⁷ Sc в поле тормозного излучения ускорителя электронов. На основе разработанной аналитической модели и метода совместной активации двух фольг установлены основные характеристики фотоядерного производства изотопов и оптимальные размеры технологической мишени. Полученные экспериментальные данные по выходу ⁴⁷Sc и основных примесных изотопов скандия в тонких фольгах из природного титана в диапазоне значений энергии электронов 35…95 МэВ позволяют уточнить имеющиеся данные по сечению реакции ⁴⁸Ti(γ,p)⁴⁷Sc. На основе этих результатов методом моделирования рассчитаны общая и удельная активность ⁴⁷Sc в цилиндрических мишенях из титана оптимальных размеров. Проведено сравнение производительности фотоядерной технологии производства ⁴⁷Sc с другими методами.